PENGARUH METODE BOILING TERHADAP KADAR VITAMIN C PADA TUMBUHAN KELAKAI (STENOCHLAENA PALUSTRIS) - Anisa Nabila Rahayu; Ni Nyoman Sri Yuliani; Dian Mutiasari (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2022)
Background: Kelakai (Stenochlaena palustris) is a local vegetable of the Dayak tribe that contains Vitamin C, and the majority is cooked by boiling. Research Objectives: The aim of this study was to determine the effect of the boiling method on vitamin C levels in the kelakai plant. Method: This research was an experimental study to test vitamin C on samples of fresh kelakai, boiled kelakai (3 minutes), and positive control using UV-Vis Spectrophotometry qualitatively and quantitatively. The results were then statistically tested. Results: The vitamin C content of fresh kelakai was 0.001704 mg/g, boiled kelakai for 3 minutes was 0.000846 mg/g, and the positive control was 0.006840 mg/g. The statistical Kruskal-Wallis test and post-hoc Mann-Whitney test showed that there were very significant differences in vitamin C levels in samples of fresh kelakai, boiled kelakai, and positive control (p =0,001). Conclusions: According to the results of statistical tests, there are differences in vitamin C levels in samples of fresh kelakai, boiled kelakai, and positive control.